PERAN ORANG TUA DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS DI SDN 1 AIR BAKOMAN KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Masrur, Muhammad; Idris, Muhammad; Pradana, Sandi (STIT AL MULTAZAM, 2021)
The purpose of this study was to determine the role of parents in increasing the learning interest of class students at SDN 1 Air Bakoman, Pulau Panggung District, Tanggamus Regency. The method used in this research is descriptive qualitative research method with data collection techniques using observations, interviews and field notes. In this study the researchers concluded that the role of parents in children's learning interest is very large, especially if the learning process is carried out at home. Parents who help the school in delivering subject matter and doing daily assignments and tests act as motivators so that children are not lazy, so that their achievements will continue to grow and improve.